2000
DOI: 10.18474/0749-8004-35.3.251
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effects on the Susceptibility of the Colorado Potato Beetle (Coleoptera: Chrysomelidae) to Beauveria bassiana (Balsamo) Vuillemin in Poland, the Czech Republic and the United States2

Abstract: Beauveria bassiana (Balsamo) Vuillemin is a fungus with broad spectrum insecticidal activity. As a biological control agent used against Colorado potato beetles (Leptinotarsa decemlineata (Say)), this fungus has performed erratically in various field studies. This inconsistent performance has been attributed to formulation problems, UV sensitivity, and humidity. In a multi-site test, B. bassiana controlled Colorado potato beetle larvae in both Poland and the Czech Republic, but not in Maryland. Control was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Warmer conditions accelerate larval development, reducing inter-molt periods, and though conidia were protected from UV degradation in the greenhouse, it has been demonstrated that acquisition of conidia from a treated substrate by CPB larvae (e.g., following a molt) is much less likely to yield a lethal dose than direct, topical-spray application (Fernandez et al, 2001). It is also well documented that the GHA strain of B. bassiana used in these tests is highly sensitive to temperatures ≥ 30ºC (Long et al, 2000;Martin et al, 2000;Inglis et al, 1996). The lowest mortality from Bb (16%) was recorded under the highest temperature conditions (mean 29.7ºC in Test 5).…”
Section: Discussionmentioning
confidence: 99%
“…Warmer conditions accelerate larval development, reducing inter-molt periods, and though conidia were protected from UV degradation in the greenhouse, it has been demonstrated that acquisition of conidia from a treated substrate by CPB larvae (e.g., following a molt) is much less likely to yield a lethal dose than direct, topical-spray application (Fernandez et al, 2001). It is also well documented that the GHA strain of B. bassiana used in these tests is highly sensitive to temperatures ≥ 30ºC (Long et al, 2000;Martin et al, 2000;Inglis et al, 1996). The lowest mortality from Bb (16%) was recorded under the highest temperature conditions (mean 29.7ºC in Test 5).…”
Section: Discussionmentioning
confidence: 99%
“…Under the wet, cool conditions of 2004, when adult population control from MX applications averaged 85%, larval populations were reduced by just 18%. Inglis et al (1997) and Martin et al (2000) attributed poor efficacy of Bb-GHA applications to hot and sunny weather conditions, but the former study was of rangeland grasshoppers, which bask to elevate body temperature above 40°C, and the latter study was conducted in Maryland during a period when average ambient temperature was >27°C. Our results suggest that Bb (and Bb-GHA in particular) is maladapted for lethal activity in the dry, highly insolated environment characteristic of row-crop canopies, even under moderate temperature conditions, and are in accord with the observations of Fargues (1972), who reported a decrease in cumulative mortality and increase in delayed mortality at temperatures >20°C; Lacey et al (1999), who observed significant Bb-GHA efficacy only after potato row closure; Inglis et al (1996), who observed marked reductions in lethal Bb-GHA mycoses among grasshoppers allowed to bask for just one hour per day; and May (1982), who found that body temperatures of CPB larvae on sunlit foliage were several degrees above ambient.…”
Section: Discussionmentioning
confidence: 99%
“…But in field applications little to no effect on the weevil population and on potato tuber damage was observed (Kühne et al, in prep.). Similar discrepancies between laboratory and field trials as well as between different field trials are reported from other B. bassiana -pest systems , Martin et al 2000. This may be due to two main reasons: Either the exposure methods (e.g.…”
Section: Methodssupporting
confidence: 66%